Budaya Kerja Aparatur Sipil Negara pada Kantor Camat Idi Tunong Kabupaten Aceh Timur - Maulina, Cut Sri; Humaizi, Humaizi; Achmad, Nurman (PERSPEKTIF, 2020)
The purpose of this study was to look at work culture and the factors that influence the work culture of employees in the Idi Tunong Subdistrict Office. Descriptive research method with a qualitative approach. Data collection techniques are through observation, interviews and documentation. The informants of this research are the key informants namely the Idi Tunong Sub-District Head and the Public and Personnel Kasubbag, the main informants are employees of the Idi Tunong Sub-District Office employee and additional informants are the people who get the services of the Idi Tunong Sub-District Office. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this study are the work culture of the Idi Tunong Sub-District Office in terms of information disclosure, mutual respect, cooperation between employees has been carried out well only in employee work discipline is still not optimal and needs to be improved. Meanwhile, for factors that influence the work culture of the Idi Tunong Subdistrict Office such as organizational culture, external culture, learning process and motivation have an influence on the work culture of the Idi Tunong Subdistrict Office, while for leader behavior, employee selection, mission clarity, mission certainty, exemplary leaders still have not influenced the work culture in the Idi Tunong Sub-District Office.